Reexpansion pulmonary edema after treatment of primary spontaneous pneumothorax - Gleibs, Fabian; Döllinger, Felix; Witzenrath, Martin; Huebner, Ralf-Harto; Saccomanno, Jacopo (Pneumologie, 2023)
A 24-year-old male patient, without further symptoms or comorbidities presented to the emergency room with acute dyspnea after heavy lifting two days before. On auscultation an attenuated vesicular breath was noticed on the right lung. In the initial chest radiograph a right-sided primary spontaneous pneumothorax with minor mediastinal shift was diagnosed. After insertion of a 12-French chest tube the patient’s clinical condition deteriorated. The following chest radiograph and computed tomography of the thorax showed a reexpansion pulmonary edema in the right lung. The patient was admitted to the ICU and supportive treatment was initiated. Pulmonary reexpansion edema after drainage of a pneumothorax is a very rare complication with mortality rates reaching up to 20%. The exact pathophysiology remains unknown. Typical Symptoms include dyspnea, hypotension, and tachycardia. To minimize the risk of a pulmonary reexpansion edema, not more than 1200–1800 ml of air should be drained at once and the drainage should be stopped when the patient starts coughing.
Keywords: pneumothorax; dyspnea; chest tube; unilateral pulmonary edema